The Art of Communicating with Brain, Heart, and Soul: An Islamic Perspective on Neurophilocommunication - Anurogo, Dito; Sasmita, Niken Sasadhara; Syarif, Ubed Abdilah; Awaliah, Nur Rahmah; Rachman , Budhy Munawar; Jia Yi Wang (王 家儀) , Jia Yi Wang (Universitas Muhammadiyah Surakarta, 2023)
Communication in the digital age has been transformed into more complicated ways due to various mediums and platforms based on information technology and digital devices. The digital age has brought about complex changes to communication through the use of technology and digital devices. It has more threats as well as benefits and innovations. In the meantime, many people who engaged in communication don’t fully take advantages but fall into miscommunication due to lack of digital literacy. In particular, in the field of health services, the threats of digital communication would make people, for instances the patients, in danger. While it offers benefits and innovations, it also brings new threats, particularly in the field of healthcare where miscommunication can harm patients mentally and physically. The miscommunication, misunderstanding etc. would harm their health mentally and physically. To address these issues, it is crucial to explore and analyze communication from multiple perspectives using scientific approaches. Hence, thinking and research on communication is extremely important. Various scientific approaches should be applied to analyze and sharpen communication in multiple perspectives. This manuscript discusses soft-skills of communication in the field of health issues of the digital era. This study is an attempt to invent the theoretical foundation of the ways in communication throughout analytical and philosophical approaches. It is Neurophilocommunication (NPC) that comprise of thoughts in communication that could be applied in the field of health issues on digital base and platforms.This study proposes NPC, a concept combining communication and neuroscience to enhance communication in healthcare in the digital era. The goal is to establish a theoretical foundation for effective communication and to improve the health outcomes of patients.